Star formation in the bars of nearby galaxies - Ngcebetsha, Buntu (Department of Astronomy, 2016)
Aims: In this study, we quantify the star formation activity in bars as a function of the host stellar mass and the morphological type. We use a sample of 70 barred spiral galaxies in the nearby universe taken from the Spitzer Survey of Stellar Structure in Galaxies (S⁴G). The data are combined with Hα data from various optical telescopes. (KPNO, JKT, OHP and CTIO) Methods: We overlay continuum-subtracted Hα emission on 3.6μm images from Spitzer (S⁴G) to quantify the distribution of star formation in each bar. We discern the star formation distribution into three classes: morph-(1): Minimal to no star formation in the bar but intense star formation activity at the bar ends and in the nuclear region; morph-(2): Star formation along the bar, in the nuclear region to the bar ends; morph-(3): Star formation only at the bar ends. To understand the location of the bar and its properties, we used ellipse fitting to identify the bar properties, including the bar size and the bar strength. We also use the host stellar mass of each galaxy measured from the 3.6μm integrated magnitudes from S⁴G to investigate how the three star formation distributions are related to the stellar mass. The host galaxies are divided into Early-Type (SB0-SBbc) and Late-Type Barred Spirals (SBc-SBm) - these morphological types correlate with a variety of galaxy properties that have historically been used to better understand galaxy formation and evolution. For the next stage of this work, we will compare the star formation activity in one galaxy from the sample, NGC 1097 with molecular gas distribution mapped using ALMA. This will be an investigation of the relationship between gas kinematics and star formation using numerical simulations of gas flow. [Please note: this thesis fulltext has been deferred until 9 December 2016]